RESIDENTS’ PERCEPTION OF FLOODING AND MITIGATION IN A PERIURBAN AREA OF DELTA STATE, NIGERIA - Jakpor, Joe; Akpovwovwo, Ufuoma (FUDMA JOURNAL OF SCIENCES, 2026)
This study investigated flooding characteristics and mitigation measures in a periurban area of Delta State, based on the perception of the residents. Specifically, it identified the causes and effects of flooding in the study area, examined the strategies used for flood mitigation, evaluated public perceptions of flood disaster mitigation measures, and assessed the level of community participation in the implemented mitigation strategies. Primary data were collected through a questionnaire survey in which 400 questionnaires were distributed across five selected communities. Secondary data on flood characteristics, including type or category, causes, impacts, duration, and flooding patterns, from 2005 to 2024, were obtained from the government emergency management agency. The results showed that the average inundated area during flood events was 6.31 km², while the mean flood length and width were 2.10 km and 2.10 km, respectively. The longest flood duration recorded spanned eight weeks. The data were analyzed using Chi-Square at a 0.05 level of significance. 61% of respondents considered existing flood mitigation measures to be ineffective, while 66% indicated that they were unaware of any flood mitigation initiatives in their communities. A significant association was discovered between public awareness and flood hazard readiness (p < 0.05, where p = 0.010). Overall, the study demonstrates that flood risk perception plays an important role in the effectiveness of mitigation efforts. This study therefore recommends awareness and an increase in community involvement through collaborations between government agencies and the communities.